Human ecosystems in critical areas - Yanitsky, Oleg N. (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The author attempts to evaluate the recent terrorists attacks in the light of his concept of critical areas. The theoretical differences between the concepts of the critical areas and of a state of emergency are explicated with a focus on processes of socio-ecological metabolism. Using the ecosystem method he considers the response of various levels of a human community, from global to local, i.e. from international to individual: global, national, group and individual. The article is ended with the following preliminary conclusions. First, the critical areas are usually spatially fixed whereas a state of emergency is indifferent in its scale and consequences. Second, the major features of terrorists, type of human ecosystems are the following: unseen, maximum closed, network-structured, armed and aimed at the distraction of the existing social order. Third, any state of emergency is a kind of all-embracing risk in its utmost form. It cannot be conquered by one mighty strike of a state power. The struggle against terrorism is a multisided and long-term process. Four, Schools, universities, sciences and media should not only to inform people but teach them how to behave in critical cases. Five, the terrorism can be represented and studied as a specific human ecosystem. Six, any critical system seriously changes an existed man-nature social metabolism. Seven, a study of an extreme way of life is as important as normal one. Eight, in the global risk society all social institutes should be prepared to respond to the emerging risks locally, i.e. here and now. Terrorism as a social phenomenon is a high-level risk but urges state and civil society to work hand in hand. Ten, the kind of socio-ecological metabolism is an indicator of stability of any social order.